Design and Evaluation of Virtual Reality Educational Content for Managing Multiple Trauma Victims in Emergency Medicine Students of Iranshahr - Somayeh Farmad; Navaz Emadi; Elahe Akvan (Reviews in Clinical Medicine)
Background: Effective trauma management requires specialized skills, and advanced technologies such as Virtual Reality (VR) can enhance medical education. This study aimed to evaluate the effectiveness of VR-based educational content in training emergency medicine students on managing multiple trauma victims. Materials and Methods: This educational study involved 40 emergency medicine students who were randomly assigned to two groups. The first group underwent VR-based training in pairs (two students per team) over four sessions, focusing on multiple trauma scenarios. The second group practiced scenario simulations using moulages. Both groups received feedback after each session and had the opportunity to repeat the scenarios. Results: In this study, the performance of 40 emergency medicine students was evaluated using pre- and post-tests. The results demonstrated that both educational methods—Virtual Reality and live simulation—significantly enhanced student performance. A comparison between the two approaches revealed no significant difference in effectiveness, as both methods led to comparable improvements. Conclusion: Virtual Reality was recognized as an effective tool for teaching trauma management and could be widely used in clinical education. However, further studies are necessary for a more comprehensive evaluation and to establish the effectiveness of this technology in educational settings.